Analysis of Variables Affecting Brand Loyalty in Junior Crocodile Products at Paragon Mall Semarang - Junaidi, Achmad; Hendrayati, Selvia; Nindhita, Yoga; Sari, Oki hardiyanti Rukmana (Management Analysis Journal, 2020)
This study aims to determine the impact of brand communication and brand image on brand loyalty both directly and through brand trust. This research was conducted in the city of Semarang, and as a population are consumers of Crocodile Junior products in Paragon Mall Semarang. The sample used amounted to 100. Data collection techniques using accidential sampling. Primary data in this study were obtained from the distribution of closed question questionnaires. Data analysis techniques used multiple linear regression analysis with the application of SPSS 24. The results showed that the brand communication variable significantly influenced the brand image with a significance of 0,000 <0.05. Brand pronunciation has a significant effect on brand trust with a significance of 0,000 <0.05. Brand image has a significant effect on brand trust with a significance of 0,000 <0.05. Brand trust has a significant effect on brand loyalty with a significance of 0,000 <0.05. Based on the sobel test, the brand image variable can be a moderating variable between brand communication and brand trust with z sobel 6.778> z score 1.96. Besides, brand trust can be a moderating variable between brand communication and brand loyalty with z sobel 3,813> z score 1.96. Brand trust can be a moderating variable between brand image and brand loyalty with z sobel 7,365> z score 1.96.